Odpowiedzi

2010-02-23T15:44:51+01:00
6(x+y)=10y
y-x=0,5

6x+6y=10y
y-x=0,5|*6

6x+6y=10y
6y-6x=3
+_________(ten uklad równan podkreslasz i dajesz znak dodac)

6x+6y+6y-6x=10y+3(6x i -6x skracają się)
12y=10y+3
12y-10y=3
2y=3|:2
y=1,5

y-x=0,5
1,5-x=0,5
-x=0,5-1,5
-x=-1:(-1)
x=1

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^
2(2x-y)+3(x+3y)=42
5(x+3y)-8(2x-y)= -32

4x-2y+3x+9y=42
5x+15y-16x+8y=-32

7x+7y=42|*11
-11x+23y=-32|*7

77x+77y=462
-77x+161y=-224
+______________

77x+77y-77x+161y=462-224(77x i -77x skracają się)
238y=238|:238
y=1

7x+7y=42
7x+7*1=42
7x+7=42
7x=42-7
7x=35|:7
x=5

*-mnożenie

mam nadzieje że pomogłam::)